Prakiraan Kebutuhan Energi Listrik Di Wilayah PT. PLN (Persero) Rayon Bangkinang Menggunakan Prangkat Lunak LEAP (Long-Range Energy Alternatives Planning System) - Riko Oklantama; Suwitno Suwitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The growth amount of Kampar Regency resident is 14.57%, is growth has increased the need of electrical energy. Therefore to make the electrical consumption supply at Kampar Regency sustainable, it needs electrical energy consumption forecast. This paper purposes electrical demand forecasting for 2016-2025 to predict the level of consumption (demand) of electricity per sector tariffs for PT. PLN (Persero) Rayon Bangkinang regency. Data required for this research was included PLN data on the number of customers and energy consumption in each tariff level sub period 2014-2016 and data of alternative energy potential (Biogas) in kampar regency is utilized as a source of electrical energy. The mechanism of forecasting is composed by following processes, firstly demand is calculated based on the amount of electrical energy consumption activity and the amount of electrical energy consumption per activity (energy intensity). Next, once those data is obtained and it is calculated and analyzed by LEAP (Long-range Energy Alternatives Planning System). In the end the result will compared to data from PT. PLN. In 2016, base PLN data was 17.868 MWh. In other hand, the data from LEAP software was 17.868 MWh. The difference is only on energy consumption of one sector while in household sector from PT. PLN was 12.844 MWh, but data obtained from LEAP software was about 12.845 MWh. The results obtained from the electrical energy demand forecast is totally in the year 2016-2025 shows a positive trend that is increasing from 17.868 to 43.514 MWh. The average growth per year is 10,39%. With so large number growth in demand for electrical energy in the region of PT. PLN (Persero) Rayon Bangkinang, it is needed a new plant that will be able to fill the needs of electrical energy in the future. In kampar regency by 2015 there are 30.473 cows that can be used for biogas energy sources, the potential of electrical energy that can be utilized from cows dung processing into biogas energy is 21,273 MW.Keywords: LEAP (Long-range Energy Alternatives Planning System), energy consumption prediction, electrical energy demand forecast.